Avaliação da prevalência de sintomas respiratórios em duas categorias de trabalhadores portuários avulsos : estiva e conferentes de carga - Kolhy, Lélio Marcus Munhoz (2014)
Introdution: Port sundry workers (TPAs) develops its activities on board or on the side of ships, loading and unloading operations at sea, whose volume handled at the Santos port reached 104 million tonnes in 2012, of which 50.7 million tonnes were of solid bulk, considered an important source of particulate matter (PM) from the fugitive emissions and its own characteristics. The assessment of air quality in the places where they operate the bulk carriers is relevant to the study of health of TPAs. Objective: To evaluate the prevalence of respiratory symptoms in two categories of port laborers broadsides: stowage and cargo lecturers. Methodology: cross-sectional study, performed by applying an investigative questionnaire, inquiry terminated anonymous European Community Respiratory Health Survey (ECRHS), covering the cargo stowage and lecturers, to identify the circulatory system disorders and metabolic and chronic respiratory diseases (CKD) and assess the prevalence of symptoms suggestive of asthma and chronic bronchitis. The exhibition was evaluated through samples of concentration levels of respirable fine particulates (MP2 .5) collected in nine campaigns during operations of embarkation of sugar and unloading of wheat, corn and soybean meal and compared with the data of MP2 .5 obtained on mobile monitoring station of the company of Environmental sanitation technology (CETESB), Ponta da Praia - Santos. Descriptive analyses were made of all variables and t-test or U Mann-Whitney test to compare the measures of MP2 .5. The Chi-square test was used to verify associations between qualitative variables and study groups. The significance level adopted in tests was of 5%. Results: the main health problems presented by the study group are the circulatory system disorders, with 32.0% and 17.3% of affirmative responses to hypertension and the metabolic system disorders, with 12.0% and 14.7% of affirmative responses to diabetes, respectively, for the lecturers of loading and stowage. Already with respect to respiratory diseases 20.0% and 13.3% have breathing problems and 4.0 and 9.3 have asthma/bronchitis, respectively, also for the lecturers of cargo and stowage. The main frequency of affirmative responses to symptoms suggestive of asthma and chronic bronchitis of the ECRHS inquiry was the manifestation of an allergy in the nose or allergic rhinitis, for both categories. The average level of the port was measured MP2.5 to 37.78 ± 13.31 and the station of CETESB was 13.85 ± 15.40 (p<0.0001). Conclusion: The TPAs are exposed to an average of 12:0 am upper air quality standards proposed by the World Health Organization (who) and its maximum concentration enough to achieve the quality considered bad by State Decree No. 59.11313. The average concentration of MP2 .5 in the port is about 2.7 times larger than the station registered by CETESB. This exposure increases the risk of harms to health, as noted by the significant percentage of circulatory system disorders and metabolic and respiratory diseases, particularly asthma and chronic bronchitis.